(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2020)
The province of Guayas has very few available keys for Diptera larvae development identification with forensic pourpuses. To identify insects in preimaginal stages, it is required to wait for the specimen to become adult to determine its identification, which limits its use in forensic science. The present work focuses on describing the ontogeny of entomofauna of forensic relevance associated with decomposing viscera. The families registered during the sampling were Sarcophagidae, Calliphoridae and Muscidae. The first flies to colonize the bait belong to the. Three morphometric characteristics relevant for identification and differentiation between stages and families were detected: cephalic capsule, anterior spiracle, gills of the anterior spiracle and internal dorsal tubers. On the other hand, larval development period vary between families, with Sarcophagidae being the group with the longest period. The information presented in this work will facilitate the taxonomic identification of insect samples obtained from decomposing bodies, with the possibility of estimating post-mortem intervals (PMI).